Association of CD58 Polymorphisms and its Protein Expression with the Development and Prognosis of Autoimmune Thyroid Diseases. (17th February 2020) - Yamamoto, Mayu; Watanabe, Mikio; Inoue, Naoya; Watanabe, Ayano; Ozaki, Haruka; Ohsaki, Mizuki; Hidaka, Yoh; Iwatani, Yoshinori
ABSTRACT: The prognosis of autoimmune thyroid diseases (AITDs), including Graves' disease (GD) and Hashimoto's disease (HD), varies among patients. The interaction of CD58 and its ligand (CD2) promotes the differentiation of regulatory T cells and suppresses the immune response. To clarify the association of CD58 expression with the pathogenesis and prognosis of AITDs, we genotyped polymorphisms in the CD58 gene including rs12044852A/C (SNP1), rs2300747A/G (SNP2), rs1335532C/T (SNP3), rs1016140G/T (SNP4), rs1414275C/T (SNP5) and rs11588376C/T (SNP6). The CD58 SNPs were genotyped in 177 GD patients, 193 HD patients and 116 healthy volunteers (control subjects). We used the Polymerase chain reaction-Restriction Fragment Length Polymorphism (PCR-RFLP) method for the genotyping of SNP1 and SNPs3-6 and the TaqMan® SNP genotyping assay for the genotyping of SNP2. The frequencies of the AA genotype in SNP1 tend to be high in all patients with AITDs than in control subjects, although it was not significant. The GG genotype of SNP2, the CC genotype of SNP3, the TT genotype of SNP4, the CC genotype of SNP5 and the CC genotype of SNP6 were all significantly more frequent in patients with AITDs than in control subjects. The proportion of CD58 + cells in monocytes was significantly lower in healthy individuals with each of these risk genotypes of AITDs and lower in GD and HD patients than that in healthy controls. In conclusion, CD58 SNPs are involved in AITD susceptibility through the reduction in CD58 expression, which probably suppresses regulatory T cells.